An Overview of Strategies for Re-Engagement of Patients with Loss to Follow-Up Therapy for Arv ODHIV - Eko Septian Insiano; Bagoes Widjanarko; Antono Suryo Putro (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the strategy of re-engaging Loss patients to follow up ARV therapy for people with HIV/AIDS. The method used in this research is qualitative with a case study approach. The results of this research were obtained through analysis using deductive analytic which focuses on tracing and mentoring strategies, barriers, and partnerships. follow-up HIV/AIDS ARV therapy, namely a patient-centered approach (client-centered approach) with the tracing method via telephone contact, physical tracing/home visit and virtual tracing, Barriers to re-engagement of patients who stop or are absent from ARV HIV/AIDS care , that is. patient contact numbers are not available, patients do not have a permanent residence, partnerships between NGOs and service personnel have been going well, this is evidenced by the existence of an MOU between PEKA NGOs and Health Services/PKM Keywords: Re-Engagement, Loss to Follow-Up, HIV, Strategy